An ambient-temperature stable nanoparticle-based vaccine for nasal application that confers long-lasting immunogenicity to carried antigens - Cruz-Resendiz, Adolfo; Acero, Gonzalo; Sampieri, Alicia; Gevorkian, Goar; Salvador, Carolina; Escobar, Laura; Rosendo-Pineda, Margarita Jacaranda; Medeiros, Mara; Vaca, Luis (Frontiers in Immunology, 2022)
Polyhedrins are viral proteins present in a large family of baculoviruses that form occlusion bodies (polyhedra). These structures protect the virus particles from the outside environment until they are ingested by susceptible insects. Occluded viruses can sustain inclement weather for long periods of time. Therefore, the polyhedra is a natural preservative that keeps the viral structure intact at ambient temperature for years. In a previous study we identified the first 110 amino acids from polyhedrin (PH(1-110)) as a good candidate to carry antigens of interest. As a proof of concept, we produced a fusion protein with PH(1-110) and the green fluorescent protein (PH(1-110)GFP). The fusion protein associates spontaneously during its synthesis resulting in the formation of nanoparticles. Nasal immunization with these nanoparticles and in the absence of any adjuvant, results in a robust immune response with the production of IgG immunoglobulins that remained elevated for months and that selectively recognize the GFP but not PH(1-110). These results indicate that PH(1-110) is poorly immunogenic but capable of enhancing the immune response to GFP.